Analisis Tingkat Stres Mahasiswa dalam Menulis Tugas Akhir (Skripsi) di STIE Pembangunan Tanjungpinang - Cindy Emilia; Dimas Pangestu; Flora Akyuwen; Nurul Hannisya Pahlevi; Sairin Prayoga; Eka Kurnia Saputra (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
A thesis is a scientific paper written by students to complete their undergraduate program (S1). The thesis writing process is often a source of excessive stress for students, caused by various factors that can hinder the work, such as difficulty in finding journals, difficulty in obtaining research objects, inability to find relevant phenomena in the objects studied, and challenges for students who work to balance work and college assignments. This study aims to analyze the level of stress of students in completing their thesis. The method used is qualitative with a phenomenological approach. Data collection was carried out through the snowball sampling technique, where researchers interacted with a number of relevant participants and collected primary data. Data collection techniques include participant observation, in-depth interviews, and distributing questionnaires to students. Data analysis was carried out using descriptive analytical and percentage methods. To ensure the validity of the data, this study applies the triangulation technique, where the data obtained supports each other. The results of the study provide an overview of the level of stress of students in compiling a thesis, factors that trigger stress symptoms, and the impacts caused by the stress.